The Impact of the Eto'o Tower Building Construction Process on the Quality of Life of Local Communities in Suco Motael, Posto Administrativo Vera Cruz, Municipio Dili, Timor–Leste - Ximenes, Jacinto Marques; Surjono, Surjono; Efani, Anthon (Postgraduate School of Universitas Brawijaya, 2024)
Out in a limited manner, especially in constructing small-scale buildings to improve the community's economy. However, the development was not controlled, and there was even unlicensed construction. This study aims to describe the impact of the Eto'o Tower construction process on the quality of life of the local community and explore the driving and inhibiting factors of the Eto'o Tower construction process on the community's quality of life. This type of qualitative research is based on observations of existing data in the field and data obtained from in-depth interviews asked of informants. The result presents if the environmental development impacted by construction brings partial effects, both positive (space improvement that could enhance the development and opportunity of modernization) and negative (Physical Damage and Decreasing Environmental Conditions). Despite both effects, these constructions also reflect the evidence of driving factors (government commitment, the enthusiasm of the surrounding citizen's community for participating, and the opportunity for foreign investors to invest in various sectors by adding new places) and inhibiting factors (the partial chain problems caused by the presence of illegal permits that affect the surrounding environment). Overall, government policies due to building construction activities are still lacking, so there is a need for socialization, guidance, and supervision by relevant government agencies. Keywords: development permits, quality of life of the community, development of the area